2010
DOI: 10.1111/j.1532-7078.2009.00020.x
|View full text |Cite
|
Sign up to set email alerts
|

Learning While Babbling: Prelinguistic Object‐Directed Vocalizations Indicate a Readiness to Learn

Abstract: Two studies illustrate the functional significance of a new category of prelinguistic vocalizing-object-directed vocalizations (ODVs)-and show that these sounds are connected to learning about words and objects. Experiment 1 tested 12-month-old infants' perceptual learning of objects that elicited ODVs. Fourteen infants' vocalizations were recorded as they explored novel objects. Infants learned visual features of objects that elicited the most ODVs but not of objects that elicited the fewest vocalizations. Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
92
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(95 citation statements)
references
References 64 publications
3
92
0
Order By: Relevance
“…This category included any vocalization produced by the infant except infants' fixed signals (e.g., cries, shouts, laughs or groans) or vegetative sounds (e.g., sneezes or burps) (Nathani & Oller, 2001;Oller et al, 2010). Following these authors, we coded vocalizations as independent utterances when they were separated by a silence longer than 300 ms. Then, following Goldstein et al (2010) and Gros-Louis et al (2014), we coded infants' gaze direction as pertaining to one of the following categories: stimulus-directed (looking at the target stimulus presented in the trial), experimenter-directed (looking at the experimenter after seeing the target stimulus), looking-caregiver (looking at the caregiver in the moment after seeing the target stimulus), looking-other (looking at other objects in of the room like the books or the bead toy, to a stimulus visually present in the room like the pig or light, or to the caregiver/experimenter when they were not previously looking at the target stimulus). We only included as vocalizations those that clearly referred to the target stimulus, that is, were stimulus-directed, and also those that were experimenter-directed after the child had seen the stimulus.…”
Section: Coding and Reliabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…This category included any vocalization produced by the infant except infants' fixed signals (e.g., cries, shouts, laughs or groans) or vegetative sounds (e.g., sneezes or burps) (Nathani & Oller, 2001;Oller et al, 2010). Following these authors, we coded vocalizations as independent utterances when they were separated by a silence longer than 300 ms. Then, following Goldstein et al (2010) and Gros-Louis et al (2014), we coded infants' gaze direction as pertaining to one of the following categories: stimulus-directed (looking at the target stimulus presented in the trial), experimenter-directed (looking at the experimenter after seeing the target stimulus), looking-caregiver (looking at the caregiver in the moment after seeing the target stimulus), looking-other (looking at other objects in of the room like the books or the bead toy, to a stimulus visually present in the room like the pig or light, or to the caregiver/experimenter when they were not previously looking at the target stimulus). We only included as vocalizations those that clearly referred to the target stimulus, that is, were stimulus-directed, and also those that were experimenter-directed after the child had seen the stimulus.…”
Section: Coding and Reliabilitymentioning
confidence: 99%
“…Likewise, research on infants' gesture production has shown that communicative gestures (e.g., iconic and pointing gestures) signal intentional communication (Bates et al, 1979;Bavin et al, 2008;Caselli, Rinaldi, Stefanini, & Volterra, 2012) and that pointing gestures with a declarative intention are a good predictor of the emergence of verbal language (Colonnesi, Stams, Koster, & Noom, 2010). On the other hand, literature on speech development has also documented that acoustic measures of early infants' vocalizations vary depending according to their communicative intentionality (Esteve-Gibert & Prieto, 2014) and that vocalizations coordinated with gaze directed at the referent affect adult-infant social interactions and support language learning (Goldstein, Schwade, Briesch, & Syal, 2010;Gros-Louis, West, & King, 2014). While some studies with slightly older infants have shown that one particular use of supplementary gesture-speech combinations -that in which the gesture modality conveys a different meaning than the one conveyed by speech -predicts the onset of grammatical development (Capirci, Iverson, Pizzuto, & Volterra, 1996;Iverson & Goldin-Meadow, 2005;Özç aliskan & Goldin-Meadow, 2005;Pizzuto, Capobianco, & Devescovi, 2005;Rowe & GoldinMeadow, 2009), the emergence of simultaneous gesture-speech combinations (i.e., gesture co-occurring with speech to express the same meaning) and their relation to later language development has not been analyzed in detail.…”
Section: Introductionmentioning
confidence: 99%
“…In the prelinguistic phase, gesture, particularly pointing (appearing around 11 mo) has arguably received the lion's share of attention in the literature [10]. However, there is a growing body of experimental work suggesting that early vocalizations (present from around 5 mo) are also important communicative signals [18], [19].…”
Section: B Controlling For Other Measures: Ids Ses and Infant Commmentioning
confidence: 99%
“…For example, encouraging production of vocalisations together with other communicative behaviours (e.g., eye gaze, gestures) may provide infants with more effective means of conveying communicative messages. Vocalisations combined with other social cues may be more salient to caregivers, enhancing the likelihood of an adult response, and they may also provide additional clues about the focus of the child’s attention (e.g., Goldstein, Schwade, Briesch, & Syal, 2010). In addition, coaching parents to recognize and respond to less salient or less developmentally advanced forms of communication (e.g., give/request gestures) with rich verbal input linked to infants’ current focus of attention may provide infants with increased opportunities for communicative exchange.…”
Section: Discussionmentioning
confidence: 99%